COVID-19 in prisons: a study of habeas corpus decisions by the São Paulo Court of Justice - Natalia Pires de Vasconcelos; Maíra Rocha Machado; Daniel Wei Liang Wang (Revista de Administração Pública, 2020)
Abstract Brazil has become the epicenter of the COVID-19 pandemic in the Global South-a pandemic that disproportionately affects vulnerable populations, especially those detained and imprisoned. Legal institutions are struggling to respond. In this paper, we focus on the National Council of Justice’s Recommendation 62, issued March 17, 2020, which recommends that judges take several measures to reduce the risk of COVID-19 infection in prisons. We test this recommendation’s impact by looking at habeas corpus decisions in the São Paulo Court of Justice. The exploratory findings presented here indicate that Recommendation 62 has little impact on habeas decisions. In general, citing the recommendation does not lead the Court to grant early release or house arrest to those detained, and most habeas actions are decided against petitioners. This is true even when petitioners claim to be part of a risk group, or their alleged offense did not involve violence or serious threat-factors that should favor habeas relief under Recommendation 62.